Primary abdominal gas gangrene: a report of two autopsy cases - George S. Stoyanov; Deyan L. Dzhenkov; Lilyana Petkova (University of São Paulo, 2021)
Primary hepatic gas gangrene is a form of primary abdominal gas gangrene. The condition is caused by Clostridium perfringens, other clostridia, and non-clostridia bacterial species producing gas. Unlike classical gas gangrene or myonecrosis, the disease develops without a wound or a port of entry. Instead, gas-producing bacteria in the gastrointestinal tract colonize an underlying pathological process with foci of necrosis, producing excessive gas and spreading hematogenously to other organs. Herein we present two autopsy cases of primary hepatic gas gangrene diagnosed on autopsy, with the gross and histological changes that can be considered specific for this rare condition. Both patients had severe underlying liver disease-prone for this entity development. The gross changes in the cases are postmortem subcutaneous emphysema, skin bullae with pooled blood, pneumothorax, pneumoabdomen, abundant gas in the circulatory system, porous structure of the internal organs (tissue gas bubbles), and advanced tissue lysis, not corresponding to the post mortem time. Histology showed optically empty areas of varying size in the internal organs, which weave the structure of the organs and rod-shaped bacteria with scarcity or complete absence of inflammatory reaction.